(3HUjQI GdMVQI GdCMeOjI GdTGgjI HSjQI GdMVQI GdCMeOjI GdfHhjIs - (3eMeO Hf YeQ Hf eHGQc GdMejQj GdMVQej, HMQb , SQGL GdOjf ,J (B930 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi cTa YfG GdZeI CeG HYO , aEf NjQ GdgOi gOi eMeO Udi Gddg Ydjg hSdeeaJJMkG HNWHJf , efbSekG Edi bSejf eTJedkG Ydi SjQJjf s
(3BNQgG (B:s
(3adjbd ai BNQ eLdSg ChMjf jbhe (B: (3SHMGf QHc QH GdYRI YeG jUahf , hSdGe Ydi GdeQSdjf , hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3HHYV GdehGVY HjGVs
(3Ydi ghGeTgG JUMjMGJs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B207 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B89s
Keywords: (3GdJGQjNs